Bioaccumulation of The Heavy Metal Lead (Pb) in Herbivorous and Carnivorous Fishes Within The Seagrass Ecosystem of Nusmapi Island - Sembel, Luky; Manangkalangi, Emmanuel; Manumpil, Abraham W; Lutfi; Tebaiy, Selvi; Manan, Jemmy; Lefaan, Paskalina T.; Paisey, Anjeli S; Loinenak, Frida; Kolibongso, Duaitd (Sam Ratulangi University, 2026)
Nusmapi Island, located in Doreri Bay, Manokwari Regency, West Papua Province, is exposed to various anthropogenic activities that may introduce pollutants transported from the mainland. Fish are commonly used as bioindicators of aquatic pollution due to their ability to accumulate contaminants through food webs. This study was conducted on Nusmapi Island from June to August 2020 to examine differences in lead (Pb) concentrations among fish species and trophic groups. Fish samples represented two trophic groups: carnivores and herbivores that feed on algae and seagrass. Pb concentrations in fish muscle were analyzed using a Shimadzu AA-6880 atomic absorption spectrophotometer (AAS). The results showed that the average Pb concentration in the carnivorous group was 0.88 mg/kg, while the herbivorous group exhibited a higher average concentration of 1.13 mg/kg. The highest Pb concentration was recorded in Siganus spinus (1.34 mg/kg), whereas the lowest concentration was found in Neoniphon sammara (0.27 mg/kg). Elevated Pb levels in sediments and seagrass around Nusmapi Island may exert continuous environmental pressure on marine biota. As Pb concentrations in these environmental compartments exceed threshold levels, they may serve as major sources of contamination entering the food chain, increasing the toxicological risk for fish occupying higher trophic levels. Keywords: heavy metal Pb, bioaccumulation, Doreri Bay Abstrak Pulau Nusmapi merupakan daerah yang berada di kawasan Teluk Doreri Kabupaten Manokwari yang merupakan daerah yang terdampak akibat padatnya berbagai aktivitas dari daratan yang ditransport secara langsung maupun tidak langsung. Ikan merupakan organisme yang sering digunakan sebagai bioindikator untuk menilai tingkat pencemaran suatu perairan. Penelitian dilakukan pada bulan Juni - Agustus Tahun 2020. Sampel ikan yang diambil terdiri dari dua kelompok trofik, yaitu karnivora dan herbivora yang memakan alga dan lamun. Tujuan utama penelitian ini adalah menguji perbedaan konsentrasi Pb berdasarkan spesies dan kelompok trofiknya guna memahami distribusi polutan di wilayah tersebut. Daging ikan sebanyak 30 g hingga 50 g diambil pada bagian punggung, selanjutnya daging ditimbang lalu dibungkus dengan aluminium foil. Daging ikan di destruksi dan dianalisis dengan atomic absorbtion spectrophotometer (AAS). Konsentrasi Pb pada kelompok karnivora adalah sebesar 0,88 mg/kg, sedangkan pada kelompok herbivora sebesar 1,13 mg/kg. Konsentrasi tertinggi ditemukan pada Siganus spinus (1,34 mg/kg), sementara konsentrasi terendah pada Neoniphon sammara (0,27 mg/kg). Mengingat logam Pb telah melampaui ambang batas pada sedimen dan lamun akan menjadi sumber utama polusi yang masuk ke dalam rantai makanan dan pada akhirnya menempatkan ikan sebagai tingkat trofik yang lebih tinggi pada posisi rentan secara toksikologis. Kata kunci: logam berat Pb, bioakumulasi, Teluk Doreri